Algae from continental waters of La Pampa (ARGENTINA) I Vol vocales and Chlorococcales (Chorophyta) (Semiárida, 2020)
Volvocales and Chlorococcales from Continental waters of La Pampa Province are studied; a11of them are new records for this province. Among the algae observed, six taxa, including varietes and forms are new records for Argentine.Trabajo realizado en el Lab. de Ficología, UBA, con una pasantía de CRUN, 1983. Presentado en 11J. de Geol. l.P. y I J. de Biol. l.P. 1983. Fac. Cs. Exac. Nat. UNLPam.